Pengaruh Pemahaman Perpajakan, Kesadaran Wajib Pajak Dan Kemauan Membayar Pajak Terhadap Kepatuhan Wajib Pajak Pelaku UMKM - Chitia Liviana Kurniawan; Rohma Septiawati; Ade Trisyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to gain comprehensive insights into the impact of tax literacy, taxpayer awareness, and willingness to pay taxes on tax compliance among Small and Medium Enterprises (SMEs). Employing a quantitative methodology, the research involved sixty respondents who underwent an outlier process to complete a questionnaire. Data analysis encompassed descriptive statistics, classical assumption tests, and hypothesis testing. The findings indicate that tax comprehension has a significant influence on SME tax compliance, both partially and simultaneously. However, taxpayer awareness and willingness to pay taxes did not demonstrate a substantial effect on tax compliance levels within the SME sector.